Measuring pro-poor growth in China from 2000 to 2015 - Ou Jiajia (2021)
Existing studies stop short of the analysis of China’s pro-poor growth with updated data and comparisons of different regions, as well as lacking in considering the influences of different poverty lines. This thesis studies the pro-poorness of the growth in China from 2000 to 2015 using three indexes from Kakwani and Pernia (2000), Ravallion and Chen (2003), and Kakwani, Khander and Son (2004) respectively, applied to the geographica regions which was organized into three groups to compare the results of more and less developed regions, confronting the east and the west, urban and rural, coastal and non-coastal regions. The analysis was conducted under the poverty lines of $1.25/day and $1.90/day. The results displayed that growth, from 2000 to 2015 in China, is weakly pro-poor or trickle down. Growth in the west, rural and non-coastal areas, the poorest regions, is not more pro-poor than growth in the east, urban and coastal areas, indicating that the more developed regions have more balance growth. The policy implications are the need to introduce corrective measures to avoid widening the gap between the more developed and less developed regions.